Caracterização morfológica da plataforma continental de Icapuí utilizando dados batimétricos - Abreu Neto, João Capistrano de (2019)
The bathymetric surveys are presented as a tool through which we can obtain morphological information, such as bathymetric profiles, digital terrain models, slope and relief orientation, having applications such as identification of sandbanks, engineering works, navigation charts and environmental studies. Previous works on the morphology of the continental shelf of Icapuí, where bathymetric surveys were carried out in the western sector of the inner platform, identified rocky outcrops, results of coastline variations, cliff testimonies that resisted coastal processes in the region and a field of submerged dunes. Due to a lack of a characterization of the platform as a whole, this work aims at the morphological characterization of the continental shelf of the city of Icapuí using bathymetric data to identify the most expressive bottom forms of the area. This way, it was possible to characterize the morphology of the area, which is predominantly flat with low slope, being narrower and shallower than the average of the rest of the state of Ceará, with approximately 45 km long and with the shelf breaking zone with average depth of 45 m. There were still identified in the inner platform submerged beach ridges and a break in the continuity of the relief, that makes it possible to divide the area in east and west sectors. Satisfactory results were obtained, making it possible to identify the most expressive structures in the area, being possible to relate them to the sea level fluctuations, making the region of interest for the understanding of such events.